STUDY OF THE EFFECT OF VARIOUS FACTORS ON THE SYNTHESIS OF VINYL ESTERS OF WINE ACIDS - Okhundadaev, Abdugani (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Fruit acids and their vinyl derivatives are widely used as biologically active substances in agriculture, medicine and industry. Adding a vinyl group to the acid molecule to increase its reactive active centers, thereby further increasing its biological activity, is one of the urgent tasks. Potassium-sodium salt of tartaric acid NaKC4H4O6·4H2O is used in chemical analysis and radio technology under the name of segnet salt. In this paper, complicated vinyl esters of dibasic carboxylic acids, including wine acid, are synthesized in a homogeneous solution of the solvent dimethylformamide in the presence of zinc acetate and AlCl3-6H2O catalysts, along with a description of the spectra of the end products.